2015
DOI: 10.3747/pdi.2013.00161
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Mycobacterium chelonae Peritoneal Dialysis-Related Infection by a Combination Regimen Including Local Thermal Therapy

Abstract: As depicted in Figure 1, the catheter was situated quite far down into the scrotum. With the use of straight catheters, an excessively long intra-abdominal portion of the catheter can lead to increased tension with the potential to increase the risk of catheter migration. Some authors address the issue of preventing catheter tip migration by suture fixation to the pelvis (11,12). In our experience suture fixation is associated with a significant increase in catheter-associated pain post operatively. A previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…One case report demonstrated successful treatment of M. chelonae peritoneal dialysis catheter related infection with use of thermal therapy in addition to antimicrobials [15] . Thermal sensitivity of M. chelonae and inability to grow on higher temperature was the basis of the success of this mode of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One case report demonstrated successful treatment of M. chelonae peritoneal dialysis catheter related infection with use of thermal therapy in addition to antimicrobials [15] . Thermal sensitivity of M. chelonae and inability to grow on higher temperature was the basis of the success of this mode of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no definite exit site care protocol for significantly reducing ESIs due to NTM. Recently, Okado et al [ 10 ] reported the effectiveness of a local thermal therapy using disposable pocket warmers for treating ESIs due to M. chelonae in addition to combined antibiotic therapy and exit site cleaning with 10% povidone-iodine solution; in this case, the patient was successfully treated without catheter removal. Local thermal therapy might be effective for treating ESIs because M. chelonae prefers lower temperatures and grows best at 30°C [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kunin et al [ 11 ] reviewed 11 cases of PD-associated peritonitis due to M. chelonae , including their own case, and reported that ESI was diagnosed in 4 cases (36%) and catheter removal was performed in 10 (90%). We identified 5 previously reported cases of ESI caused by M. chelonae in the literature (ESIs with comorbid peritonitis were excluded) [ 10 , 12 , 13 , 14 ]. Including the present case, catheter removal was performed in 4 cases (67%), and 4 cases (2 patients required catheter reinsertion but the other 2 did not) were able to continue PD (67%) (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%